2021
DOI: 10.1016/j.stem.2020.10.015
|View full text |Cite|
|
Sign up to set email alerts
|

CRISPR-Mediated Induction of Neuron-Enriched Mitochondrial Proteins Boosts Direct Glia-to-Neuron Conversion

Abstract: Summary Astrocyte-to-neuron conversion is a promising avenue for neuronal replacement therapy. Neurons are particularly dependent on mitochondrial function, but how well mitochondria adapt to the new fate is unknown. Here, we determined the comprehensive mitochondrial proteome of cortical astrocytes and neurons, identifying about 150 significantly enriched mitochondrial proteins for each cell type, including transporters, metabolic enzymes, and cell-type-specific antioxidants. Monitoring their trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 66 publications
3
38
0
Order By: Relevance
“…GSEA (Figures S3H and S3I; Data S2) confirmed the enrichment for genes involved in synapse formation and neuronal activity for both TF-mediated reprogramming cascades. The few genes commonly downregulated (Figure 4F) were involved in detoxification (Figure 4G; Data S2) and b-oxidation (GSEA; Figures S3J and S3K; Data S2), well-known astrocyte hallmarks (Russo et al, 2020).…”
Section: Molecular Characterization Of Ascl1-and Neurog2-insmentioning
confidence: 99%
See 1 more Smart Citation
“…GSEA (Figures S3H and S3I; Data S2) confirmed the enrichment for genes involved in synapse formation and neuronal activity for both TF-mediated reprogramming cascades. The few genes commonly downregulated (Figure 4F) were involved in detoxification (Figure 4G; Data S2) and b-oxidation (GSEA; Figures S3J and S3K; Data S2), well-known astrocyte hallmarks (Russo et al, 2020).…”
Section: Molecular Characterization Of Ascl1-and Neurog2-insmentioning
confidence: 99%
“…Pioneered by in vitro conversion of astrocytes from the cerebral cortex (Berninger et al, 2007;Heinrich et al, 2010;Heins et al, 2002), this approach is often based on the expression of proneural factors (e.g., Ascl1 and Neurog2), master regulators and pioneer factors in the conversion process both in vitro (Berninger et al, 2007;Masserdotti et al, 2015;Smith et al, 2016;Vierbuchen et al, 2010;Wapinski et al, 2013) and in vivo (Guo et al, 2014;Liu et al, 2015;Mattugini et al, 2019;Rivetti di Val Cervo et al, 2017;Torper et al, 2013). Cortical astrocyte cultures allowed identifying major reprogramming hurdles (Gascó n et al, 2016;Russo et al, 2020), whose manipulation in vivo led to improving the reprogramming efficiency from 10% to over 90% (Gascó n et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In cortical astrocytes, mitochondria have elongated shapes consistent with mitochondrial fusion ( Motori et al, 2013 ), while neurons exhibit smaller mitochondria, consistent with mitochondrial fission ( Misgeld and Schwarz, 2017 ). Strikingly, Ascl1 -iNs generated from murine P5 astrocytes also undergo a transition to a fission-like smaller mitochondrial morphology ( Russo et al, 2020 ). Furthermore, LC-MS/MS of mitochondria from cortical neurons and astrocytes revealed a large number of differences, and a neuronal mitochondrial phenotype was recapitulated in Ascl1 -iNs to varying degrees, depending on the extent of neuronal conversion ( Russo et al, 2020 ).…”
Section: Direct Neuronal Reprogramming In Vitromentioning
confidence: 99%
“…Strikingly, Ascl1 -iNs generated from murine P5 astrocytes also undergo a transition to a fission-like smaller mitochondrial morphology ( Russo et al, 2020 ). Furthermore, LC-MS/MS of mitochondria from cortical neurons and astrocytes revealed a large number of differences, and a neuronal mitochondrial phenotype was recapitulated in Ascl1 -iNs to varying degrees, depending on the extent of neuronal conversion ( Russo et al, 2020 ). Finally, strikingly, the importance of differences in mitochondrial content was demonstrated by co-expressing Ascl1 with neuronal-enriched antioxidant genes Sod1 and Prdx2 , which augmented astrocyte to iN lineage conversion ( Russo et al, 2020 ).…”
Section: Direct Neuronal Reprogramming In Vitromentioning
confidence: 99%
“…Additionally, researchers argued that methods that undergo an intermediate stage reduce oxidative stress and promote a safer reprogramming process (Gascón et al, 2016). One study reported that CRISPRa (activating)-mediated early induction of mitochondrial proteins improved metabolic conversion and reprogramming efficiency (Russo et al, 2020).…”
Section: Astrocytesmentioning
confidence: 99%